Religious based education of Islamic elementary school, being competitive with market management strategies - Wahyudhiana Wahyudhiana (Institut Agama Islam Negeri (IAIN) Salatiga, 2018)
Education is the foremost factor to escalate nation esteem, so all countries in the world are intense in developing education system to meet the more complexity of life. This research aims to find out the phenomena of educational institution managed as an industry or corporation in terms of positioning, management branding, management marketing, marketing strategy, promotion strategy, in order to achieve customer satisfaction by improving the education quality as intangible services from industrial perspective. The research context takes place in Islamic Elementary School, Madrasa Ibtidaiya Istiqomah (MII) Sambas Purbalingga as a religious based education with competitive and marketable market management strategies, and it has 1.329 students in 38 classes. This research belongs to qualitative descriptive in which the researcher actively involves in the location by interviewing the informants and taking documentation to support the research. The result shows that the school is excellent and prominent, professionally organized by the management of customer satisfaction orientation with management patterns and models: Total Quality Management, Madrasa Based Management and ISO Management (International Standard Organization). The principles of school marketing management focus on: 1) positioning, attaching in customer mind; 2) differentiation, different from conventional program and; 3) branding, maintaining the brand. Those are the attractiveness toward customers to enroll their children in this institution.